2021
DOI: 10.1055/s-0041-1741111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Race, Ethnicity, and Socioeconomic Status on Nasopharyngeal Carcinoma Disease-Specific and Conditional Survival

Abstract: Introduction Race, ethnicity, and socioeconomic status (SES) are complex, interconnected social determinants of health outcomes. This study uses multivariable analysis on a combination of large national datasets to examine the effects of these factors on 5-year disease-specific survival (DSS) and conditional DSS (CDSS) for nasopharyngeal carcinoma (NPC). Methods A retrospective study of adults with NPC between 2000 and 2017 from the Surveillance, Epidemiology, End Results (SEER) registry was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Receiving adjuvant therapy requires a number of regimented postoperative visits that can be difficult to adhere to, and disparities in utilization of such therapy have been documented for a number of different tumors. [35][36][37][38][39] Mechanisms of this disparity include travel difficulties as well as other barriers including factors as simple as parking costs. 40,41 Finally, another study by Yu et al found that oral cancer patients of certain racial/ethnic/ socioeconomic backgrounds were less likely to be treated in high-volume hospitals than their more advantaged counterparts which can result in poor utilization of standard of care or more extensive treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Receiving adjuvant therapy requires a number of regimented postoperative visits that can be difficult to adhere to, and disparities in utilization of such therapy have been documented for a number of different tumors. [35][36][37][38][39] Mechanisms of this disparity include travel difficulties as well as other barriers including factors as simple as parking costs. 40,41 Finally, another study by Yu et al found that oral cancer patients of certain racial/ethnic/ socioeconomic backgrounds were less likely to be treated in high-volume hospitals than their more advantaged counterparts which can result in poor utilization of standard of care or more extensive treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these recommendations, our study identified variations in utilization of multimodal therapy for patients with certain racial and socioeconomic backgrounds even after controlling for stage of disease in multivariable models. Receiving adjuvant therapy requires a number of regimented postoperative visits that can be difficult to adhere to, and disparities in utilization of such therapy have been documented for a number of different tumors 35–39 . Mechanisms of this disparity include travel difficulties as well as other barriers including factors as simple as parking costs 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Slight elevations in NPC mortality have been noted in regions along the Gulf and Atlantic Coasts; however, the higher mortality rates in coastal regions could not be explained by significant geographic variations in mortality 43 . It is possible that slight differences in economic sub‐regions might explain slight elevations and stationary trends in NPC, since the disease is associated with lower socioeconomic status 3,44 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for rhinologic malignancies, patients of minority demographic groups and lower socioeconomic status appear more likely to present with advanced stage disease 9–12 . Considering that such disorders are quite rare at baseline, this disparity suggests that as a specialty, our collective datasets lack proportionally representative demographic minority patients with early‐stage cancer.…”
mentioning
confidence: 99%
“…Furthermore, for rhinologic malignancies, patients of minority demographic groups and lower socioeconomic status appear more likely to present with advanced stage disease. [9][10][11][12] Considering that such disorders are quite rare at baseline, this disparity suggests that as a specialty, our collective datasets lack proportionally representative demographic minority patients with early-stage cancer. What would these data yield when used as input for a machine-learning algorithm programmed to screen radiology studies or histopathology of biopsies for, say, malignant conversion of inverted papilloma?…”
mentioning
confidence: 99%